New insights on the Holocene marine transgression in the Bahía Camarones (Chubut, Argentina) - Zanchetta, Giovanni (2012)
The stratigraphic reconstruction of the northern sector of theBahía Camarones (Chubut, Argentina) allowed to improve ourunderstanding of the Holocene marine transgression in the area.The first phase of the maximum of the transgression, is interpretedas dominated by the high rate of eustatic rise of sea level until ca.6-7 ka BP possiblyassociated to sedimentary starvation as suggestedby fossil accumulation. After this first phase, the general trend indi-cates a progressive fall of the relative sea level after the MiddleHolocene high stand as documented in other parts of south Amer-ica Atlantic coast. Our data, coupled with the robust radiocarbondata set available for the area from literature, indicate three mainlocal steps of coastal aggradation between ca. 6600 and 5400 yr BP(ca. 7000-5600 yr cal BP), ca. 3300 and 2000 yr BP (ca. 3100-1700 yrcal BP), and ca. 1300-500 yr BP (ca. 1000-300 yr cal BP). A signifi-cant age gap in coastal aggradation is present between ca. 5300 and4400 yr BP (ca. 5600-4500 yr cal BP), and perhaps between ca 2000and 1300 yr BP (ca. 1700-1000 yr cal BP). These can be linked tophases of local sea level fall and/or phases of sedimentary starvationand/or changes in drift transport which can have produced localcoastal cannibalization. However, no conclusive data can beadvanced. Data obtained from careful measurements of sea levelmarkers represented by the top of marsh and fluvial terraces indi-cate lower values for the sea level estimation compared with thedata set previously proposed for the area. This stigmatizes the factthat field-oriented works are still the priority in the Patagonia coastalong with accurate age measurement, especially for obtaining thefundamental information we need for predicting the environmentalimpact, in these coastal areas,from accelerate sea level rise as effectof global warming.